What's wrong with lookism? personal appearance, discrimination, and disadvantage - Mason, Andrew J. ca. 20.Jh.- (Oxford University Press, 2023)
"People are treated differently as a result of their appearance. Those regarded as overweight are regularly disadvantaged by their body shape or size when they apply for jobs; it is often harder for them to find romantic partners; and they are vulnerable to harassment and bullying in various settings, such as at school or on social media. The treatment they receive may be rooted in appearance norms that apply demanding aesthetic standards to body shape and size, or have its origins in prejudices that express moral criticism by associating higher weight with a lack of self-discipline. People with prominent tattoos are often treated less favourably in employment decisions and in their everyday encounters as a result of conventional attitudes that are sometimes laced with moral judgements concerning the sanctity of the natural body, or influenced by prejudices that link extensive tattoos with aggression or mental health problems. Afro-textured hairstyles are frequently regarded as unsuitable for the workplace, motivating restrictive appearance codes that disproportionately affect members of racial groups whose hair is naturally suited to being worn in these ways. Short men are commonly regarded as less attractive; they are disadvantaged not only when it comes to dating but also in terms of their career prospects"
Keywords: Sozialphilosophie; Aussehen; Unterprivilegierung